COVID-19 Pandemic and Dentistry in Turkey: Evaluation of the Second Year and Recommendations - Karamüftüoğlu, Nevra; Atasoy Ulusoy, Özgür İlke (Turkey Health Literacy Journal, 2021)
Today, the emergence of deadly viruses and global epidemics threaten the world health system and economy. The SARS-CoV-2 infection, which started as an epidemic in Wuhan, China, was declared as a COVID-19 pandemic by the World Health Organization and later caused havoc between different countries and continents. Dentistry is considered to be the occupational group with the highest risk of contracting COVID-19, due to the close range of communication and dental procedures and the possibility of exposure to aerosol droplets. Dentists and auxiliary staff must use full personal protective equipment to protect themselves and their patients. In this review, it is aimed to evaluate the existing literature in the light of the guidelines published by the Ministry of Health of the Republic of Turkey, the Turkish Dental Association and the World Health Organization, and to determine the status of COVID-19 infection in dentistry in Turkey in the second year of the pandemic and make recommendations.